Subgrain boundaries in single crystal blade airfoil of aircraft engine. Issue 8 (16th June 2017) - Bogdanowicz, W.; Krawczyk, J.; Tondos, A.; Sieniawski, J.
Abstract : The growth defects of single crystal turbine blades of aircraft engine, made of Ni‐based superalloy were analysed. The highest number of growth defects was revealed near the tip of the blade airfoil. It is caused by the formation of additional defects of thin‐walled airfoil area near the root, and their propagation toward the tip of the blade. The number of defects located near the tip of airfoil can be determined using the model described in the paper. Abstract : The single crystal turbine blades of aircraft engine were obtained by directional solidification of Ni‐based superalloy via Bridgman technique at withdrawal rate of 5 mm/min. The CMSX‐4 industrial alloy were used for crystallization. After crystallization the blades were subjected to heat treatment. The Laue diffraction, X‐ray diffraction topography and SEM methods were used to investigate the subgrain structure of blade airfoils. It was stated that subgrain boundaries with the misorientation angle ranging from over a dozen to a few dozen angular minutes occurred in the airfoil. The number of low‐angle boundaries in the cross‐section near the tip of the blade airfoil is higher than that in the cross‐sections located near the root area. It is caused by formation during crystallization of additional low‐angle boundaries in thin‐walled airfoil area and their propagation toward the tip of airfoil. The number of low‐angle boundaries in cross‐section located near the tip of airfoil can be determined by three mechanisms: dendrites "deflection" on surface of mould; creation of internal stress regions in the thin‐walled area of blade airfoil and propagation of two additional boundaries from root to the airfoil.